Integration and retention of American physician assistants/associates working in English hospitals: A qualitative study. Issue 5 (May 2020) - Taylor, Francesca; Drennan, Vari M; Halter, Mary; Calestani, Melania
Highlights: Lack of role clarity and role boundary tensions impacted early integration experiences. Adaptation and development of skills helped meet the needs of medical teams. Finding a niche work role positively influenced integration and retention. Supervising doctors seemed instrumental in creating role development opportunities. Abstract: Background: Health workforce planners in many high-income countries are considering policy strategies to retain home and overseas-trained health professionals. There is a lack of evidence on how hospitals can successfully integrate and retain skilled overseas professionals in relevant work roles. This study aimed to explore the integration and retention experiences of skilled American physician assistants/associates working in English hospitals. Methods: A qualitative study using semi-structured telephone interviews was undertaken in spring 2017 and spring 2018. Data were coded and analysed using thematic analysis. The study was framed within a theoretical model of role development. Results: Nineteen physician assistants/associates participated in interviews at timepoint one, and seventeen at timepoint two, across seven English hospitals. Four themes were identified in the integration and retention processes experienced by participants: motivations and expectations, seeking role identity, acceptance and integration, and establishing a niche role. Supervising doctors appeared instrumental in creating opportunities through training and system adjustment that enabled development of niche roles; offering an effective match between participant skills and interests, and medical/surgical team or organisational needs. Whether or not they had a niche role influenced the decision of participants to remain or leave. Conclusion: Integration approaches that maximise the value of the skilled health professional to the medical/surgical team and support retention, including development of optimum roles, require time and resources.